Perancangan Furniture Set untuk Aktivitas Keluarga di Ruang Keluarga pada Area Hunian - Stella Dewi (Intra, 2017)
Based on the needs of the family, the living room is the center of the house. It is the center of all family members and all activities where all family members can sit together to get entertainment. Due to its function as a gathering space for families, the living room should have enough space for all family members to gather and sit together. The design of furniture sets for family activities in the residential area is a design which aims to create furniture that can accommodate the complex user activities in the family room.The design of the furniture set has 3 alternative options. Each set is not only designed to meet complex user activities, but is also applied to different furniture with different systems. Furniture sets are expected to accommodate the activities of users for a long time (sustainable). In other words, the furniture sets can be changed to fit the needs and activities of the growing and ever changing family. This furniture design is designed for the development of infant to toddler age, but  still can be used when the child grows bigger by utilizing it into other facilities and functions. The existence of this design gives new ideas on the market to solve existing problems in the living room.